Satellite-derived land surface temperature: Current status and perspectives - Li, Zhao-Liang; Tang, Bo-Hui; Wu, Hua; Ren, Huazhong; Yan, Guangjian; Wan, Zhengming; Trigo, Isabel F.; Sobrino, José A. (Remote sensing of environment, 2013)
Land surface temperature (LST) is one of the key parameters in the physics of land surface processes from local through global scales. The importance of LST is being increasingly recognized and there is a strong interest in developing methodologies to measure LST from space. However, retrieving LST is still a challenging task since the LST retrieval problem is ill-posed. This paper reviews the current status of selected remote sensing algorithms for estimating LST from thermal infrared (TIR) data. A brief theoretical background of the subject is presented along with a survey of the algorithms employed for obtaining LST from space-based TIR measurements. The discussion focuses on TIR data acquired from polar-orbiting satellites because of their widespread use, global applicability and higher spatial resolution compared to geostationary satellites. The theoretical framework and methodologies used to derive the LST from the data are reviewed followed by the methodologies for validating satellite-derived LST. Directions for future research to improve the accuracy of satellite-derived LST are then suggested. ► Current status of satellite-derived land surface temperature is reviewed. ► Methodologies for validating satellite-derived temperature are also reviewed. ► Directions for future research are suggested.